Living the Teaching Practicum Within Dichotomies: The Story From Within When Implementing ICTs in the English Language Classroom - Sandra Viviana Pinzón Capador; Carmen Helena Guerrero Nieto (Asociación Colombiana de Profesores de Ingles, 2018)
This article reports the results of an introspective research conducted by a student-teacher and her advisor. Both met regularly over a period of one year and a half as part of the student-teacher academic work for the Research I class. As a result of their conversation the student-teacher and her advisor decided to document the former's experience during her teaching practicum as she was trying to implement an innovation using m-learning in a public school in Bogotá. The analysis of data (narrative introspection, introspective interview, and lesson plans) shows that the student-teacher lived her teaching practicum within dichotomies in three dimensions we named negotiating between epistemologies, making up for logistic/technological flaws, and mending the self: between frustration and achievement.